2002
DOI: 10.1007/s00264-001-0311-7
|View full text |Cite
|
Sign up to set email alerts
|

Core decompression in early stages of femoral head osteonecrosis – an MRI-controlled study

Abstract: We treated 45 hips with idiopathic necrosis of the femoral head stages I-III with core decompression. Average age of patients was 41 (27-68) years and average follow-up 68.9 (31-120) months. In 30 hip joints in stage I, 29 showed no radiographic progression and a complete remission of the changes consistent with necrosis on MRI at the last follow-up. In 27 patients the clinical resultbased on the Harris Hip Score (HHS) assessment -was excellent (average HHS 91.9 points). Of nine hips in stage II, four had rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 20 publications
1
36
0
2
Order By: Relevance
“…Limited data exist in the literature documenting successful results in controlled trials at 5-and 10-year follow-up on patients that have undergone core decompression of the hip. Existing studies have indicated promising results that meet or exceed these goals after core decompression, but control groups are often inadequate [1][2][3][4][5][6][7][8][9][10][11]. More rigorous evaluation of core decompression is required to document its true efficacy and resulting cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Limited data exist in the literature documenting successful results in controlled trials at 5-and 10-year follow-up on patients that have undergone core decompression of the hip. Existing studies have indicated promising results that meet or exceed these goals after core decompression, but control groups are often inadequate [1][2][3][4][5][6][7][8][9][10][11]. More rigorous evaluation of core decompression is required to document its true efficacy and resulting cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, core decompression is likely to have poor cost-effectiveness in these cases of latestage disease. Patients with extensive femoral head involvement or a history of long-term steroid use are also likely to demonstrate clinical efficacy below these levels [3][4][5][6][7][8][9][10][11]. The use of core decompression in these subgroups is not supported in this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations